2021
DOI: 10.3390/su132413852
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review on the Research Progress of Mindfulness and Its Implications at the Workplace

Abstract: Mindfulness has rapidly become a significant subject area in many disciplines. Most of the work on mindfulness has focused on the perspective of health and healthcare professionals, but relatively less research is focused on the organizational outcomes at the workplace. This review presents a theoretical and practical trajectory of mindfulness by sequential integration of recent fragmented scholarly work on mindfulness at the workplace. The review showcases that most contemporary practical challenges in organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 197 publications
(265 reference statements)
0
9
0
1
Order By: Relevance
“…This helps value-based management to create a new source of motivation, namely the idea of using work to concretize political ambitions by imbuing professional achievements with technical quality. The ultimate aim here is the wellbeing of each and every person involved [68,69], a project that can be implemented quite prudently thanks to new technologies (company social networks, learning communities, collaborative innovations, etc.) that were made possible by social innovations themselves enabled by postmodern management pursuing a dual mission: the creation of human relationships and the development of meaning.…”
Section: Values-driven Organizationsmentioning
confidence: 99%
“…This helps value-based management to create a new source of motivation, namely the idea of using work to concretize political ambitions by imbuing professional achievements with technical quality. The ultimate aim here is the wellbeing of each and every person involved [68,69], a project that can be implemented quite prudently thanks to new technologies (company social networks, learning communities, collaborative innovations, etc.) that were made possible by social innovations themselves enabled by postmodern management pursuing a dual mission: the creation of human relationships and the development of meaning.…”
Section: Values-driven Organizationsmentioning
confidence: 99%
“…En los contextos educativos, favorece al rendimiento académico y al bienestar psicológico de los alumnos (Viciana et al, 2018;López-Hernáez, 2016). En las organizaciones laborales, contribuye a la satisfacción y rendimiento laboral, resiliencia psicológica, motivación, y salud física de los trabajadores (Panditharathne & Chen, 2021;Goilean et al, 2020). Existen aproximaciones para el desarrollo de la Inteligencia Emocional utilizando el mindfulness (Goleman, 2013, pp.227-251).…”
Section: Mindfulness O Atención Plena Y Su Relación Con La Creatividadunclassified
“…Previous research has also demonstrated MBIs in workplace settings to be effective in enhancing well-being as well as reducing perceived stress and self-reported symptoms of depression and anxiety (Vonderlin et al, 2020). Furthermore, a recent integrated review of the effect of mindfulness in the workplace demonstrated effects on both work-related well-being and organizational outcomes, such as enhanced leadership qualities and better interpersonal relationships 10.3389/fpsyg.2023.1112907 Frontiers in Psychology 03 frontiersin.org (Panditharathne and Chen, 2021). On the basis of findings from previous research, the World Health Organization (WHO) mentions 5 MBIs as potential beneficial interventions to strengthen mental health in the workplace in their recent publication from Autumn 2022 (WHO, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Where the effects of MBIs on the mental health of individuals are well-documented ( De Vibe et al, 2017 ; Panditharathne and Chen, 2021 ; van Agteren et al, 2021 ), less in known about the potential impact of such MBIs on entire organizations. However, based on the evidence of effects of MBIs on individuals, Good et al (2015) propose mindfulness to be effective in improving the psychosocial work environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation